Peningkatan Kompetensi Pelayanan Nasabah melalui Simulasi Transaksi Penyetoran dan Penarikan Tabungan pada Siswa SMK Nurul Yaqin - Ahmad Zubadul Afiq; Khittah Ashilah; Farida Umi Choiriyah; Achmad Fawaid; Moh. Jeweherul Kalamaiah (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2026)
Customer service is a crucial aspect of Islamic financial institutions, requiring technical skills, communication skills, attention to detail and a professional attitude. The limited practical experience of vocational school students in handling Islamic savings transactions formed the background to this community service initiative. This activity aims to enhance the customer service competencies of students at Nurul Yaqin Vocational School through training, transaction simulations, and practical mentoring in collaboration with lecturers from the Faculty of Sharia Economics and Business and the Wirolegi Branch of BMT Nusantara. The activity employed a participatory approach comprising the stages of needs identification, training, service simulations, and evaluation. Data was collected through observation, documentation, interviews, as well as pre-tests and post-tests. The results of the activity demonstrated an improvement in participants’ competencies, as evidenced by an increase in the average pre-test score from 61.40 to 86.70 in the post-test—a rise of 41.21 per cent. In addition to improved understanding, the students also demonstrated development in transaction skills, customer service communication, administrative accuracy, and self-confidence. This initiative demonstrates that practice-based learning through collaboration between educational institutions and Islamic financial institutions is capable of supporting improvements in students’ employability in line with the needs of the industry.